Unlawful Acts in Determination of Joint Property and Donations Study of Decision Number 190/Pdt.G/2018/Pn.Kpg - Desia Banjarani; Muslim Nugraha; Syahri Ramadhan; Sri Handayani (Journal of Private and Commercial Law, 2024)
Analysis of Padang District Court Decision Plaintiff Name Aleta Salomi Derica Kale-Pa Number 190/Pdt.G/2018/PN.Kpg., concerning joint property grants. The legal issues raised in this analysis are: How is the analysis of the determination of joint property in Decision Number 190/Pdt.G/2018/PN.Kpg? And how can grants and control over the object of the grant be categorized as unlawful acts in Decision Number 190/Pdt.G/2018/PN.Kpg? The method used in this analysis is the IRAC Method which is a legal reasoning method with issue analysis (I), rule of law (R), argument (A), and conclusion (C). Several legal issues analyzed from the decision are to determine the object of the grant, in this case land, which is joint property, the judge's first step is to prove that the plaintiff and the landowner are husband and wife as evidenced by the Marriage Certificate. Then the next proof is related to the determination of joint property as evidenced by the land sale and purchase document. Regarding the sale and purchase process, it is also supported by the testimony of witnesses who in essence state that the witnesses know directly about the sale and purchase of the land. The grant in Decision Number 190/Pdt.G/2018/PN.Kpg has been declared as an unlawful act because the object of the grant has been proven to be joint property that was granted without the consent of the Plaintiff as the wife of the landowner. Thus, the grant is declared contrary to Article 36 paragraph 1 of Law Number 1 of 1974 concerning Marriage, Article 1666 of the Civil Code and Article 584 of the Civil Code. So based on the civil legal basis, the grant made by an unauthorized party must be declared null and void as an absolute nullity with all its legal consequences. Thus, according to the research, the decision of Decision Number 190/Pdt.G/2018/PN.Kpg is correct because the judge's considerations are in accordance with the concrete evidence as submitted by the parties.